A forensic examination of remnant radio galaxies and the implications for AGN life-cycles - Quici, Benjamin (Curtin University, 2023)
This thesis explores the life cycle and energetics of radio-loud active galactic nuclei (AGN) jets, using remnant radio galaxies to study the durations of AGN outbursts. Combining observational data, modelling, and simulations, a novel model-based method is developed to extract the intrinsic jet properties from the observed properties of remnant lobes. The method is applied to a wider sample to reveal the power-law nature of AGN jet kinetic power and lifetimes in the local Universe.